Makian Keode dalam Interaksi Masyarakat Sangil (Suatu Kajian Sosiolinguistik) - Pareda, Herol Herbano; Tulung, Golda Juliet; Kalangi, Leika Maria Victoria (Kajian Linguistik, 2019)
The aims of the research are to identify the lingual form of swearword keode in Sangil Language and to analyse its function based on the sociolinguistics study. The result of this research which has been found by the researcher that lingual form of swearword keode in Sangil language are various such as keode, keade, keo,kea, keodnya, kakeodang, mekakeode. Furthermore, the researcher used qualitative method to collect the data because it was naturally through social society in a community of Sangirese in Bitung city. There were some techniques which were used by the researcher such as observation, listening while the native speakers talked each other and surely the reseaacher only took the speech the contain swearword keode. The result showed that the function of swearword keode consisted of 14 usesand the functions were used in different contex of speech. Keywords:Swearword, Sangil Language, Sociolinguistics study